Novalis German Poet-European Thinker-Christian Mystic - Hiebel, Frederick (UNC Studies in the Germanic Languages and Literatures, 1954)
Originally published in 1954, Hiebel's "Novalis" was the first critical evaluation in English of the life and works of Novalis (1772-1801), the German Romantic poet of the Blue Flower, since Thomas Carlyle's essay in 1829. This book presents not only a fully rounded picture of the man, the philosopher and scientist, the writer of beautiful fairy tales, the mystic poet of Christianity, but also a thoughtful commentary on one of the most influential and fruitful periods in German intellectual life. Hiebel combines the exactness required of the scholar with the creative writer's intuitive appreciation of a great poet's works.